KARAKTERISTIK DEMOGRAFI DAN OBESITAS SEBAGAI FAKTOR RISIKO TERJADINYA GOUT ARTHRITIS - Elida Sinuraya; Flora Sijabat; Antonij Sitanggang (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Obesity is often associated with an increase in uric acid. This occurs through the process of decreasing the excretion of uric acid so that there is a buildup in the blood. This situation will trigger the occurrence of gout arthritis. This quantitative descriptive research aims to determine the characteristic picture of demography and obesity as risk factors for gout arthritis in students. Sampling was carried out with a total sampling so that 68 respondents were involved in this study. Data collection was carried out using metering tools and scales to obtain the respondent's body mass index. The collected data were analyzed using frequency distributions. Results; there were 3 respondents who were obese (4.4%), all aged 10-20 years, female 2 respondents (2.9%) and 1 person male (1.5%). Conclusion: based on the description of demographic characteristics and obesity, there are 4.4% of respondents who have a risk of gout arthritis in students